1971
DOI: 10.1159/000252373
|View full text |Cite
|
Sign up to set email alerts
|

Incontinentia pigmenti achromians(ITO)

Abstract: Four new cases of Iτo’s Incontinentia pigmenti achromians developing in 1 family, the mother and her 3 daughters, are reported by the authors. Histopathological investigations of the skin show an irregular epidermic hypochromy without pigment loss in the upper dermis, decrease and morphological immaturity of melanocytes, disturbance of keratinization with growth of large clear cells and malformation of skin appendages. The pathological correlations of I. P. achromians (Iτo) and histopathological pecularities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 4 publications
(7 reference statements)
1
15
0
Order By: Relevance
“…In this final stage of the disease, although the melanocytes are no longer active, there is no evidence at the moment to suggest that they either disappear or are replaced by Langerhans cells, as in vitiligo [1]. The state of affairs is much more akin to that reported in a somewhat similar condition, incontinentia pigmenti achromians (ITO) [3],…”
Section: Commentmentioning
confidence: 99%
“…In this final stage of the disease, although the melanocytes are no longer active, there is no evidence at the moment to suggest that they either disappear or are replaced by Langerhans cells, as in vitiligo [1]. The state of affairs is much more akin to that reported in a somewhat similar condition, incontinentia pigmenti achromians (ITO) [3],…”
Section: Commentmentioning
confidence: 99%
“…In the family by Sacrez et al [1970] and Grosshans et al [1971] the depigmented skin lesions seen in the three daughters became less obvious after the age of 3 years, histopathologic findings were not characteristic and, in addition, the skin biopsies showed decreased melanin granules but also atrophy of the sweat glands and aplasia of hair roots. Pinol et al [1969] described a mother with a zosteriform depigmented lesion that blistered repeatedly on sun and heat exposure, in whom they made the diagnosis of HI.…”
mentioning
confidence: 99%
“…In the section on inheritance the authors state that: 1) "in nearly all cases, HI occurs sporadically with no affected sibs or parents"; 2) "there may be one familial HI case" [Grosshans et al, 1971;Sacrez et al, 1970]; 3) "There are two other families with affected males" (not described in the paper); 4) "in other publications that are suggestive of familial occurrence of HI, the diagnosis is doubtful" [Jelinek et al, 1973;Montagna et al, 1991;Rubin, 1972]; and that 5) "recessive inheritance in HI is unlikely" [David, 1981;Griffiths and Payne, 1975;Masumizu, 1963]. A description is also given of the HI families reported by Patrizi et al [1987] and Vormittag et al [1992] and on twin HI patients as reported by Zappella [1993].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several modes of inberitance bave been proposed, all based on single case reports [4][5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%